Analysis of cardiac anomalies in VACTERL association. Issue 12 (December 2013) - Cunningham, Bridget K.; Hadley, Donald W.; Hannoush, Hwaida; Meltzer, Andrew C.; Niforatos, Nickie; Pineda‐Alvarez, Daniel; Sachdev, Vandana; Warren‐Mora, Nicole; Solomon, Benjamin D.
<x xml:space="preserve">Abstract</x> BACKGROUND Congenital heart disease (CHD) is estimated to affect between 3 and 5% of all newborns. Extra‐cardiac malformations are observed in 7 to 50% of patients with CHD. One relatively well‐known association that can occur in the context of CHD is VACTERL. Controversy still remains regarding the definition of VATER association and its expansion to VACTERL, the appropriate diagnostic criteria and the overall incidence. METHODS We conducted a description of a case series to characterize the cardiac findings present in a cohort of patients meeting the criteria for VACTERL association. RESULTS Forty‐six of 220 were eligible for inclusion into the study, 67% (31 of 46) had CHD. The most common CHD was ventricular septal defect, present in 18 of 31 patients (58%). There was no statistically significant association between CHD severity and the presence or absence of other VACTERL component features, specifically anorectal malformation (p = 0.18) or tracheo‐esophageal fistula (p = 0.72). CHD presence also did not correlate with the presence of tracheo‐esophageal fistula or anorectal malformation. CONCLUSION Although this study does not, by design, provide further evidence toward the questions of whether CHD is a defining feature of VACTERL association, the frequency of CHD in our cohort does lend support to it being an important medical consideration in patients with VACTERL association. Based on our experience, we strongly recommend a screening echocardiogram to evaluate for CHD in individuals with a potential diagnosis of VACTERL association. Birth Defects Research (Part A) 97:792–797, 2013. © 2013 Wiley Periodicals, Inc.